Sinema Edukasi Berbasis Problem Solving Sebagai Strategi Mengedukasi Perilaku Sexting Siswa SMP - Intan Mardatillah Nur Pamuji; Devi Permatasari; Laily Tiarani Soejanto (Universitas Muria Kudus, 2025)
Teenagers are increasingly vulnerable to internet abuse, including increasing Sexting behavior on social media. This study aims to evaluate the effectiveness of problem-solving-based educational cinema in educating Sexting behavior in junior high school students. This study used a one-group pretest-posttest design involving fifteen students selected through random sampling techniques. Data collection was carried out using the Motivation to Sexting Questionnaire (MSQ) instrument to measure students' Sexting behavior tendencies before and after the intervention. Data were analyzed using the non-parametric Wilcoxon Signed Rank Test. The results showed a significant difference between the pretest and posttest scores, indicating that the intervention was effective in reducing students' Sexting behavior. These findings indicate that problem-solving-based educational cinema can be an effective alternative intervention in guidance and counseling services in schools to prevent risky sexual behavior in adolescents. Further researchers are advised to test the problem-solving-based educational cinema technique more widely at the junior high school level so that the results are more general and applicable.